“STRUCTURALANDɳBSTUDY OF In3+SUBSTITUTED YTTRIUM IRONGARNET” - R.G., VIDHATE; R.B., KAVADE; J.M., BHANDARI; K.M., JADHAV (Innovare Journal of Sciences, 2020)
Objective: To prepare and study the In3+substituted yttrium iron garnet with reference to structural parameters and IR spectra Materials and Methods: In3+ was added in to yttrium iron garnet (YIG) with a nominal composition of Y3InxFe5-xO12 with x= 0.0, 0.2 and 0.6. The Samples were prepared by a solid-state sintering method. The samples were characterized by X-ray diffraction technique. The X-ray diffraction studies of compositions revealed the formation of single phase cubic structure with lattice constant ranging from 12.37Å to 12.44 Å. The FTIR spectra of typical samples are taken in the range of 500-4000cm-1. Results:IR spectra show typical absorption bands indicating the garnet nature of samples. Conclusion: Magneton number 'ɳB'decreases with increasing In3+ content x.